2011
DOI: 10.1111/j.1439-037x.2010.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Mediterranean Tall Fescue Cultivars to Contrasting Agricultural Environments and Implications for Selection

Abstract: Extensive livestock is a basic socio‐economic feature of the Mediterranean region whose environmental and economic sustainability depends on the ability of forage resources to withstand climatically stressful conditions. Perennial forages such as tall fescue can be a valuable alternative to annuals, if they can survive across successive summer droughts. Three‐year dry matter yield and plant survival of five cultivars of Mediterranean‐type tall fescue were evaluated in six sites of Algeria, France, Italy, Moroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…Furthermore, two out of the three experimental years were characterised by an annual precipitation about 200 mm lower than the normal values for the collection sites of accessions. Such contrasting inter-annual conditions gave us the additional opportunity to study the plastic adaptation of the eleven populations to fluctuations of weather conditions, a character that has been associated both with the productivity and the persistence of perennials (Porqueddu & González, 2006;Lelièvre et al, 2008;Molle et al, 2008;Pecetti et al, 2011). Chapman et al (2011) indicated that very few studies have so far explicitly surveyed the expression of plant traits held by perennial ryegrass cultivars over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two out of the three experimental years were characterised by an annual precipitation about 200 mm lower than the normal values for the collection sites of accessions. Such contrasting inter-annual conditions gave us the additional opportunity to study the plastic adaptation of the eleven populations to fluctuations of weather conditions, a character that has been associated both with the productivity and the persistence of perennials (Porqueddu & González, 2006;Lelièvre et al, 2008;Molle et al, 2008;Pecetti et al, 2011). Chapman et al (2011) indicated that very few studies have so far explicitly surveyed the expression of plant traits held by perennial ryegrass cultivars over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Perennial forages such as tall fescue or cocksfoot can be a valuable alternative to annuals, if they can survive across successive summer droughts. Although most of the temperate origin cultivars available on the market are not drought persistent in Mediterranean areas ), a few cultivars with summer dormancy (Volaire and Norton, 2006) can tolerate severe successive droughts and survive in environments with annual rainfall as low as 300 mm Pecetti et al, 2009Pecetti et al, , 2011. Under chronic water shortages, perennial forage species have a number of advantages in comparison to the predominantly used annual species including (i) fewer inputs with less field preparation and fertilizer requirement, (ii) year-around soil cover reducing the risk of intense soil erosion, (iii) optimal use of water throughout all seasons, thus enhancing forage production in particular in autumn when cereals and annual species are not yet established and (iv) greater flexibility because of the multiple uses of these species (grazing, hay, silage).…”
Section: å Ergon Et Al European Journal Of Agronomy 92 (2018) 97-106mentioning
confidence: 99%
“…Some of these changes affect (1) human and animal disease distribution, (2) timing and reproduction of insects and pests, (3) species diversification in wetlands (Neustupa et al 2011), (4) crop yields (Pecetti et al 2011), (5) seed production (Pons and Pausas 2012), (6) biomass production (Potithep and Yasuoka 2011), (7) plant photosynthesis (Oquist et al 1993), (8) bird migration, and (9) soil decomposition and mineralization rates. Numerous indices have been used to describe frost's impact on agriculture.…”
Section: Introductionmentioning
confidence: 99%